The relevance of site-specific data in Life Cycle Assessment (LCA). The case of the municipal solid waste management in the metropolitan city of Naples (Italy). (20th January 2017) - Ripa, M.; Fiorentino, G.; Vacca, V.; Ulgiati, S.
Abstract: Municipal Solid Waste (MSW) is an unavoidable by-product of modern societies production and consumption patterns. Envisaging waste management strategies is a complex and challenging task, influenced by technical site-specific aspects. To achieve more informed decisions, technical experts should avoid streamlined and generalized analyses, while at the same time policy-makers should increasingly rely on LCA and other biophysical assessment approaches, which can help them identifying context-specific waste hierarchies and priorities. This paper uses site-specific data in comparing different waste management routes for the Metropolitan City of Naples. The waste management of the Metropolitan City of Naples (3 million people, Campania Region, Southern Italy) in the year 2012 is investigated as a case-study, after having faced a severe waste production and disposal crisis, that has not been totally resolved yet. An extensive collection of primary data is carried out to describe the main input/output flows associated with the treatment and recovery of each single waste fraction (Mixed Municipal Solid Waste – MMSW, Organic Fraction Municipal Solid Waste – OFMSW, Recyclable Fraction Municipal Solid Waste – RFMSW). LCA results reveal that the main burdens are caused by the treatment of MMSW (i.e. mechanical biological treatment, landfill, waste-to-energy) and by the export/transport of the OFMSW outside the region (due to the lack of local treatment plants), almost in all analyzed impact categories. The identification of the weak points along the waste management chain allows a sensitivity analysis to test the influence of potential improvements by means of a scenario analysis. Six strategies, substantially differing in terms of percentage of separate collection, transportation routes and options for the disposal of residual waste, are designed and analyzed. The achieved results point out that it is possible to improve the environmental efficiency of the waste management chain locally, in so strengthening the entire waste management process. This study confirms that LCA, if carefully conducted, allows the identification of criticalities and improvement potential towards new management strategies. The use of site-specific data of full-scale waste treatment facilities and the definition of alternative waste management hierarchies may help decision-making by local public administrators and stakeholders, providing a transparent picture and deep understanding of costs and benefits for waste management at local scale. Highlights: Municipal Solid Waste (MSW) Management of Naples in the year 2012 is investigated. Six alternative scenarios for MSW management are compared by means of LCA. The use of site-specific data in LCA is crucial for decision making processes.